Differential expression of akirin gene in black tiger shrimp Penaeus monodon in response to immunostimulant administration and infections with Vibrio harveyi and white spot syndrome virus. Issue 4 (11th May 2020) - Dechamma, Mundanda M.; Mani, Madhu K.; Rajeish, Moger; Santhosh, Kogaluru S.; Akhila, Dharnappa S.; Maiti, Biswajit; Bossier, Peter; Karunasagar, Iddya; Karunasagar, Indrani
Abstract: The akirin gene, which is strictly localized in the nucleus, plays a critical role in regulating antimicrobial peptide transcription, and has parallel functions to NF‐κB signaling pathway in both vertebrates and invertebrates. In shrimp, the akirin gene is expressed as innate immunity in response to microbial infection. In the present study, expression of akirin gene in Penaeus monodon with respect to Vibrio harveyi and white spot syndrome virus (WSSV) infections and immunostimulant (β‐glucan) administration were investigated by quantitative polymerase chain reaction. The gene was expressed in various tissue samples of healthy shrimp. Maximum level of expression was immediately after V. harveyi infection, suggesting that it may be an early response gene. Gene expression was remarkably upregulated in the lymphoid organ, gill, and hepatopancreas, whereas downregulation was observed in hemocytes compared with the control. In the case of WSSV‐infected samples, the akirin gene was significantly downregulated in the lymphoid organ but there was no significant difference in expression pattern in hemocytes compared to the control. In gill tissue, maximum expression was observed after 2 hr of infection, the same in hepatopancreas. Experimental challenge of β‐glucan fed shrimp infected with V. harveyi and WSSV resulted in significant upregulation of akirin gene expression in lymphoid and gill tissue.